Celebrity Endorser dan Keputusan Pembelian untuk Generasi Z: Efek Mediasi Citra Merek - Stefany Jeane Tayl; Yunita Budi Rahayu Silintowe (University of Merdeka Malang, 2021)
The main purpose of the study was to identify the effect of celebrity endorsers on purchasing decisions mediated by brand image variables on Pond’s products. The number of samples in this study was 141 respondents who had bought Pond's products. Data collection techniques using a purposive sampling method with a questionnaire. Data were analysed with SEM AMOS 24 with the results of the study: celebrity endorser has a positive and significant effect on brand image, and brand image has a positive and significant effect on purchasing decisions, then celebrity endorser has no significant direct effect on purchasing decisions. Intervening variable testing shows that there is an indirect effect between celebrity endorsers on purchasing decisions through brand image variables.